Tindakan Konsumsi: Keniscayaan Manusia dan Hubungannya Dengan Alam: Keniscayaan Manusia dan Hubungannya dengan Alam - Yogatama, Leo Agung Manggala Yogatama; Yogatama, Leo Agung Manggala (Respons: Jurnal Etika Sosial, 2024)
Consumption is the nature of human life in its adaptation to the world. Activities include taking something from nature and returning it back to nature. Today, the act of consumption has become a serious problem and tends to threaten nature as a shared home on earth. Humans today consume more than ever, this is an excess of industrial logic and the new habitus of consumption (consumerism). Various paradigms of social change - democratic socialism to green anarchism and the use of technology - have become much of a discourse and direction on how humans can treat nature. However, these efforts have a gap in discussion from the micro side, humans as agents. Based on the study of human philosophy and psychoanalysis, human consumption is no longer based on the principle of function alone, but as a need for identity or social symbols. Anxiety and feelings of incompleteness are attempted to be eliminated by the ownership of goods and the act of consumption. Based on this, a re-reflection on the act of consumption is necessary. This is covered in various literature of figures such as Amartya Sen, Erich Fromm, and Pope Francis in the encyclical Laudato si'. Efforts to reconcile humans and nature become a new life ethic that needs to be seriously considered and implemented.